THE EFFECT OF MALACCA LEAVES (Phyllantus emblica) ETHANOLIC EXTRACT ON Plasmodium falciparum GROWTH IN VITRO - Asmilia, Nuzul; TR, T Armansyah; Aliza, Dwinna; Melia, Juli; Rahmi, Erdiansyah; Daulay, Lingga Surya Maret (Jurnal Kedokteran Hewan, 2018)
The aim of this research was to find out in vitro antiplasmodium activity of Malacca leaves (Phyllantus emblica) ethanolic extract against Plasmodium falciparum growth. In this study, Plasmodium culture contained 5% parasitemia in ring stage was cultured using candle jar method and antiplasmodial activity test was carried out using microculture. The treatments were divided into 7 groups with four repetitions. K1 as negative control group was given Roswell Park Memorial Institute (RPMI), while K2 as positive control group was given artesdiaquine. Groups K3, K4, K5, K6, and K7 group was added with 100 g/mL, 75 g/mL, 50 g/mL, 25 g/mL, and 5 g/mL of Malacca leaves ethanolic extract, respectively. Antiplasmodial activity was determined by inhibition concentration of 50% parasite growth (IC50). The data were analyzed using ANOVA and followed by Duncan test. The average of parasitemia level in group K1, K2, K3, K4, K5, K6, and K7 were 55.2515.62, 8.502.52, 8.503.00, 9.250.95, 9.002.70, 9.792.06, and 10.752.22, respectively. The average of inhibition percentage in group K1, K2; K3; K4; K5; K6; and K7 were 0.000.00%, 84.624.55%; 84.625.43%; 83.261.73%; 83.714,90%; 82.353,73%; and 80.546.83%, respectively (P0.01). The results showed that the administration of malacca leaves ethanolic extract significantly affect (P0.01) the inhibition of Plasmodium growth as compared to group K1 (negative control). Probit analysis reveals the IC50 value was 3.889 g/mL. In conclusion, all doses of malacca leaves ethanolic extract used in this study was able to inhibit Plasmodium falciparum growth with IC50 value was 3.889 g/mL.